Monte Carlo Simulation Method Highlighting on the Electron Beam Irradiation on the Structure of SARS-CoV-2 - Bardane, Adil (Moscow Univ. Phys., 2021)
The outbreak of SARS-CoV-2 resulted in more than 11 000 000 infections and over 530 000 deaths. Coronavirus (S) spike glycoproteins promote entry into cells and are the main target of antibodies. We studied the effect of electron beams on the SARS CoV-2 glycoprotein and also on RNA using Monte Carlo simulation. We demonstrated that S-SARS CoV peak glycoproteins damaged by irradiation electrons corresponding to an energy loss of approximately 1.2 keV with a damage rate of the efficiency that can be as high as [Formula: see text].